Process of Investigation of Military Members who Complete Crimes of Domestic Violence in the Military Environment - Bintara Sura Priambada; S Andi Sutrasno; Dania Rama Pratiwi (Eduvest - Journal of Universal Studies, 2022)
Domestic violence perpetrated by members of the military or the Indonesian National Armed Forces. Cases of criminal acts of domestic violence allegedly committed by unscrupulous TNI-AD soldiers at Denpom IV/5 Diponegoro Semarang are cases with a priority scale. Military Police Investigators are obliged to immediately conduct investigations into criminal cases of crimes of domestic violence since knowing or receiving reports of the occurrence of the case, this happens because, in addition to criminal acts of domestic violence are cases that are easy to prove, it is also intended that the case be completed quickly. so that it is hoped that the perpetrator can immediately serve his sentence and return to his family immediately as one of the objectives of the birth of the Law on the Elimination of Domestic Violence as stated in Article 4 letter d of the Law of the Republic of Indonesia Number 23 of 2004 concerning the Elimination of Domestic Violence, namely maintaining the integrity of the harmonious and prosperous household. The function of the Military Police agency, in this case Pomdam IV/Diponegoro, in the process of resolving criminal cases allegedly committed by TNI-AD personnel is only limited to the investigation stage. Procedures carried out in carrying out investigations include reports, complaints, being caught red-handed, submission/delegation from superiors with the right to punish (Ankum)/officers submitting cases (Papera).